The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2427.2007.01833.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective compounds in weakly and strongly pigmented copepods and co‐occurring cladocerans

Abstract: 1. The prevalence of mycosporine-like amino acids (MAAs) -a group of potential ultraviolet (UV)-photoprotective compounds -was surveyed across 11 species of freshwater copepods from 20 lakes of varying ultraviolet radiation (UVR) transparency in North America, New Zealand and Argentina. Co-occurring cladocerans were also analysed (seven species from 12 lakes). Many of the calanoid copepod populations were red with carotenoid pigmentation, allowing comparison of MAA and carotenoid accumulation as photoprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
80
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 38 publications
8
80
2
Order By: Relevance
“…Copepods had astaxanthin as the main pigment in their body, and their concentration of total carotenoids was significantly higher than that of cladocerans (average ± SE: 2.6 ± 1.4 µg mg -1 and 1.0 ± 0.5 µg mg -1 ; F = 8.8, p = 0.007). This is in accordance with the recent study of Persaud et al (2007), in which copepods had a total carotenoid concentration of 3.0 µg mg -1 , and cladocerans, 0.02 µg mg -1 . Several other studies have also reported higher carotenoid concentrations in copepods relative to cladocerans (Hairston 1979b, Partali et al 1985, Hessen & Sørensen 1990, Hansson 2004) and have related this to variation in the susceptibility to different wavelengths, food compositions and availabilities.…”
Section: Taxonomic Influence On Pigmentationsupporting
confidence: 79%
See 1 more Smart Citation
“…Copepods had astaxanthin as the main pigment in their body, and their concentration of total carotenoids was significantly higher than that of cladocerans (average ± SE: 2.6 ± 1.4 µg mg -1 and 1.0 ± 0.5 µg mg -1 ; F = 8.8, p = 0.007). This is in accordance with the recent study of Persaud et al (2007), in which copepods had a total carotenoid concentration of 3.0 µg mg -1 , and cladocerans, 0.02 µg mg -1 . Several other studies have also reported higher carotenoid concentrations in copepods relative to cladocerans (Hairston 1979b, Partali et al 1985, Hessen & Sørensen 1990, Hansson 2004) and have related this to variation in the susceptibility to different wavelengths, food compositions and availabilities.…”
Section: Taxonomic Influence On Pigmentationsupporting
confidence: 79%
“…More recent studies have also concluded that pigmented individuals survive better than pale individuals when exposed to UV radiation (Hairston 1976, Hessen 1996, and that there is a strong seasonal variation in pigment content. Subarctic Daphnia umbra synthesize melanin only during summer months, beginning immediately after ice-out (Rautio & Korhola 2002), and alpine copepods peak in their mycosporine-like amino acid (MAAs) concentrations during the open-water period (Tartarotti & Sommaruga 2006, Persaud et al 2007). Pigments and the colourless MAAs in zooplankton are mostly considered to be UV photoprotectants (Perin & Lean 2004), acting together with other photoprotectants such as antioxidants and with behavioural responses such as vertical migration.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, surface avoidance in both Daphnia and L. minutus may ultimately still be related to UVR because of vulnerability to either UV damage or UV-foraging predators. Lake Giles D. catawba are substantially less pigmented than L. minutus (Persaud et al 2007). Although decreasing their visibility to visual predators, this lack of pigmentation increases susceptibility to damaging solar radiation, which can evoke downward daytime migrations (Leech and Williamson 2001;Boeing et al 2004;Cooke et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, M. salmoides has not been examined for UV photoreceptors; however, UV photoreceptors have been detected in other teleost species such as Lepomis, Perca, Salmo, and Oncorhynchus (Loew et al 1993;Browman et al 1994;Leech and Johnsen 2003). Though not directly tested, UVR may be contributing to the enhancement of prey detection in our experimental columns, particularly on species with photoprotective compounds such as copepods (Moeller et al 2005;Persaud et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation